2012
DOI: 10.1159/000341572
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Wolbachia</i></b> Induced Cytogenetical Effects as Evidenced in <b><i>Chorthippus parallelus</i></b> (Orthoptera)

Abstract: The cytoplasmic incompatibility induced by the bacterial endosymbiont Wolbachia is attributed to chromatin modification in the sperm of infected individuals and is only ‘rescued’ by infected females after fertilization. Chorthippus parallelus is a grasshopper with 2 subspecies that form a hybrid zone in the Pyrenees in which this Wolbachia-generated cytoplasmic incompatibility has recently been described. The analysis of certain cytogenetic traits (sex chromosome-linked heterochromatic bands, nucleolar organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 99 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Here, the high variability that we have found in F strains (Zabal‐Aguirre et al ., ) suggests an ancient origin of infection and thus, a long time to evolve towards such mutualism in this grasshopper. An increment in host recombination rate has recently been proposed as another Wolbachia ‐induced effect in C. parallelus (Sarasa et al ., ). However, our evidence for any increment in fecundity is equivocal, due to the low number of crosses obtained in this study; more effort would be required to discern any Wolbachia effects on the females.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Here, the high variability that we have found in F strains (Zabal‐Aguirre et al ., ) suggests an ancient origin of infection and thus, a long time to evolve towards such mutualism in this grasshopper. An increment in host recombination rate has recently been proposed as another Wolbachia ‐induced effect in C. parallelus (Sarasa et al ., ). However, our evidence for any increment in fecundity is equivocal, due to the low number of crosses obtained in this study; more effort would be required to discern any Wolbachia effects on the females.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the presence of Wolbachia has been described in C. parallelus populations (Dillon et al ., ; Martínez et al ., ; Bella et al ., ; Zabal‐Aguirre et al ., ; Martínez‐Rodríguez, ; Sarasa et al ., ). The genus Wolbachia (Hertig & Wolbach, ) includes a diverse group of alpha proteobacteria belonging to the order Rickettsiales.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Wolbachia was detected in HTS DNA sequence datasets from six orthopteran individuals that are endemic to New Zealand, representing two families and five genera ( Macropathus sp., Hemiandrus brucei , Talitropsis sedilloti , Miotopus diversus , and two Neonetus specimens). Orthoptera elsewhere in the world are known to be hosts of Wolbachia [ 57 , 58 ], but we present the first documented cases of Wolbachia infection of any endemic New Zealand invertebrate. The samples from cave weta Macropathus sp .…”
Section: Discussionmentioning
confidence: 99%
“…CI-inducing Wolbachia present in both subspecies of Cp may contribute to the evolutionary dynamics of the hybrid zone by preventing hybridization of grasshoppers with incompatible Wolbachia strains (Zabal-Aguirre et al 2010, Zabal-Aguirre et al 2014). Furthermore, a previous study found that Wolbachia negatively affects chiasmata formation and induces spermatid malformation in hybrid males of this species; these cytogenetical effects may result in modifications of paternal chromatin that contribute to the pathology of CI (Sarasa et al 2013). …”
Section: Introductionmentioning
confidence: 86%